Efektivitas Dukungan Keluarga Terhadap Kecenderungan Minat Karir siswa SMAN 1 Palopo - Ardina; Imam Pribadi; Andi Nurhayati (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2024)
This study aims to identify the effectiveness of family support on the career interest tendencies of students at SMAN 1 Palopo. This research uses a qualitative approach with a phenomenological method, where data is collected through in-depth interviews with twelfth-grade students. Holland's Career Theory is used as a theoretical foundation to understand the relationship between students' personalities and their career choices. The research results show that family support has a significant impact on students' self-confidence and motivation in determining their career paths. Some students, like FFR, receive positive support from their families, which encourages them to pursue careers aligned with their personal interests, while students like FF face pressure from their families to choose careers that are considered safer. This research also found that schools play an important role in providing career counseling services, which help students explore their interests. In conclusion, cooperation between families, schools, and students is very important in the career decision-making process, where constructive family support can enhance students' confidence, while excessive pressure can lead to confusion and dissatisfaction.